La tradition de la cueillette du miel est-elle un frein au développement de l’apiculture dans l’Aire de Conservation de l’Annapurna (Népal) ? - Samuel Perichon; Chet Bhatta (Revue d'ethnoécologie)
The honey gathering from the colonies of the giant Himalayan honeybee (Apis laboriosa) in the Annapurna mountains of Nepal has been the subject of many reports and documentaries. Suspended in the void, brave Gurung gather gigantic comb of wax using long bamboo stems. These images have been popular around the world. The cliffs at the village of Bhujung are among the outstanding places for this activity. Every year, tourists come to attend this outdoor show. Another species of honeybees (Apis cerana) also takes up residence here which shares the part of their territory with A. laboriosa. Commercial beekeeping is common in many regions of Nepal. However, it requires movable hives, startup capital, and practical knowledge. Despite that commercial beekeeping has a good potential in the village of Bhujung, local people are still not in that route and it is against the traditions of the villagers at some extent. We observed a complex custom where religious beliefs and the pride of belonging to a culture mingled together as a social identity. This study explains how social and cultural practices associated with honey hunting can influence beekeeping practices of local hive bees; and why the inhabitants rely on knowledge and practices that are those of hunter-gatherers of honey and not those of beekeepers.